2015
DOI: 10.1159/000438517
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Herbal Formulas Si-Wu-Tang and Er-Miao-San Synergistically Ameliorated Hyperuricemia and Renal Impairment in Rats Induced by Adenine and Potassium Oxonate

Abstract: Background/Aims: Hyperuricemia is an independent risk factor for chronic kidney disease and cardiovascular disease. Here, we examined the combined protective effects of Chinese herbal formula Si-Wu-Tang and Er-Miao-San on hyperuricemia and renal impairment in rats. Methods: Rats were randomly divided into normal rats, hyperuricemic rats, and hyperuricemic rats orally administrated with benzbromarone (4.5 mg·kg-1·d-1), Si-Wu-Tang (3.78 g·kg-1·d-1) and Si-Wu-Tang plus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…Traditional Chinese Medicine (TCM) treatment for hyperuricemia has gradually attracted attention, and its efficacy has shown many advantages. Many studies have shown that the TCM formula, single drug, and active ingredients in single herb have obvious effect of reducing uric acid [ 13 – 17 ]. TCM formula of ShiZhiFang (SZF) is composed of plantago seeds, white mustard seeds, vaccaria seeds, and abutilon seeds, which has been used more than 20 years in Shuguang Hospital (Shanghai, China), and confirmed the clinical safety and efficacy of decreasing uric acid [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Traditional Chinese Medicine (TCM) treatment for hyperuricemia has gradually attracted attention, and its efficacy has shown many advantages. Many studies have shown that the TCM formula, single drug, and active ingredients in single herb have obvious effect of reducing uric acid [ 13 – 17 ]. TCM formula of ShiZhiFang (SZF) is composed of plantago seeds, white mustard seeds, vaccaria seeds, and abutilon seeds, which has been used more than 20 years in Shuguang Hospital (Shanghai, China), and confirmed the clinical safety and efficacy of decreasing uric acid [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the precise mechanism is still unknown. In recent decades, increasing evidence has revealed that hyperuricemia is a major risk factor for gout but also other metabolic disorders, including metabolic syndrome, hypertension, atherosclerosis, chronic renal diseases, and peripheral vascular diseases [10][11][12][13]. A recent animal study indicated that elevated serum uric acid level exacerbates left ventricular diastolic dysfunction in mice fed a Western diet, which also leads to other pathophysiological processes, including myocardial hypertrophy, oxidative stress, interstitial fibrosis and macrophage proinflammatory polarization [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…In traditional Chinese medicine, RA is called 'Bi Zheng', a syndrome characterized by pain; numbness of the limbs, joints and muscle; weakness of flexion and extension; and, movement disorder. Bi Zheng is caused by wind, cold, dampness, heat, amongst other processes (Guo et al 2015). The main objective of treatment is to relieve joint pain and prevent joint damage, in order to improve a patient's quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…EMS has also been studied for its anti-hyperuricaemia effect as it reduces the level of serum uric acid and suppresses the activities of xanthine dehydrogenase and xanthine oxidase (Kong et al 2004). A recent study demonstrated that EMS ameliorated renal impairment and hyperuricaemia in rats synergistically by upregulating organic anion transporters 1 (OAT1) and 3 (OAT3) (Guo et al 2015). Furthermore, EMS inhibited the inflammatory mediators in RAW264.7 cells stimulated by LPS via the NK-jB pathway (Chen et al 2014).…”
Section: Introductionmentioning
confidence: 99%